Environmental impacts of prospecting and mining in Namibian national parks : implications for legislative compliance - Mansfeld, Christina (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MA (Geography and Environmental Studies))--University of Stellenbosch, 2006.